Caracterización energética y plan de mejoramiento en el sistema eléctrico del clinker l2 de la planta cementos del oriente sede Sogamoso (2020)
The following project aims to characterize electrical energy in the manufacture of Clinker l2, a cement process from the eastern Sogamoso headquarters, which is divided into four areas: crude milling, homogenization, clinkerization, and coal grinding present on line 2 During the normal operation of this process, there were problems that generated stoppages in these areas, it was identified that these were generated by trips of motor protections, trip of totalizers and damage to electric motors, heating of conductors in the aforementioned areas. It was proposed to analyze the energy quality by updating the version of meters, software and equipment conditions present in the mentioned areas, giving way to criteria in reactive power and power factor; to reach a continuous improvement in the values of reliability, monitoring and detection of harmonics. The management in the effective selection of the meters was determined thanks to their versatility. This led us to obtain a greater analysis capacity in the electrical variables, therefore, the software has a dynamic compatibility in its interface, making it very friendly and easy. in its configuration; On the other hand, the data obtained in the equipment survey gave us an operation parameterization, as a consequence, more detailed analyzes of the performance of capacitor banks were achieved to confront the final results with the process that was being carried out.